Mimar Sinan Bibliyografyası - Mehlika Karagözoğlu (Türk Kütüphaneciliği)
Sinan the Architect is the great architect in the sixteenth century who built many buildings in the Ottoman Empire. Many academicians and researchers have written about him and his works. This study introduces ‘Bibliography of Sinan the Architect’ prepared by Selçuk Mülayim and  published by Marmara University in 2011. The book consists of eleven chapters and an alphabetical index.  These chapters are ‘General Studies, ‘Monographs of Sinan’, ‘Main Sources and Documents’, ‘Environment and Institutions’, ‘Bibliographies’, ‘Architecture Before Sinan’, ‘Architecture After Sinan’, ‘Design and Technology’, ‘Building Types’, ‘Architectural Elements’ and ‘Architectural Plastics’.